Fornix transection impairs exploration but not locomotion in ambulatory macaque monkeys. - Kwok, S; Buckley, M (2006)
Prompted by the theoretical prediction that damage to the hippocampal system should abolish exploratory behavior, the present study examined exploratory movements in control monkeys (CON) and monkeys with transection of the fornix (FNX), a major input/output pathway of the hippocampus. CON and FNX monkeys were introduced to a novel octagonal chamber for six daily sessions, each lasting 20 min. Both groups visited, punctuated by stops, the majority of the floor space of the environment in each of the sessions. The exploratory movements of CON and FNX groups were not significantly different on most of the measures taken over six consecutive days. These measures included cumulative distance traveled, number and duration of stops, traveling patterns, and proportion of time spent in each of 12 designated zones of floor space. The high degree of similarity in behavior between CON and FNX groups suggests that an intact hippocampal system is not necessary for the display of normal exploratory movement per se. On the other hand, the CON and FNX groups did behave differently on two measures. First, the CON group exhibited a decrement in distance traversed over consecutive epochs within the first test session, whereas FNX animals did not. Second, on those days in which the chamber was made visually asymmetrical, the CON animals tended to show a predilection for spending proportionally more time within one particular quadrant of the chamber. These observations are consistent with the idea that interrupting normal hippocampal system function by means of fornix transection is detrimental to learning about the spatial layout of environments. We therefore suggest that while monkeys with fornix transection still display intact locomotor and exploratory behavior patterns, their new learning of visuospatial context is impaired.